ASSESSING GLOBAL CLIMATE VARIABILITY UNDER COLDEST AND WARMEST PERIODS AT DIFFERENT LATITUDINAL REGIONS - Eleonora Runtunuwu; Akihiko Kondoh (Indonesian Agency for Agricultural Research and Development, 2008)
Effect of climate change on water balance will play a key role in the biosphere system. To study the global climate change impact on water balance during 95-year period (1901-1995), long-term grid climatic data including global mean monthly temperature and precipitation at 0.5 x 0.5 degree resolution were analysed. The trend and variation of climate change, the time series of monthly air temperature and precipitation data were aggregated into annual arithmetic means for two extreme periods (1901-1920 and 1990-1995). The potential evapotranspiration (Eo) was calculated using Thornthwaite method.The changes in mean annual value were obtained by subtracting the maximum period data from 1990 to 1995 (Max) with the minimum period data from 1901 to 1920 (Min). The results revealed that over 95-year period, mean global air temperature increased by 0.57oC. The temperature increase varied greatly in Asia, with more than 3.0oC, especially at 45-70oN, as well over the northern part of America (60-65oN) and Europe (55- 75oN). In low latitude across Asia, Africa, and South America, the variation was less than 1.5oC. In 80-85ºN region, the variation was relatively small and at higher latitudes it increasedsignificantly. Precipitation varied temporally and spatially. In the 40-45ºN and 40-45ºS regions, increasing precipitation of more than 100 mm occurred during the June-August andSeptember-November, especially in the northern hemisphere. The Eo increase of 2000 mm during 95 years occurred in the tropical northern America, middle Africa, and South-East Asia. A grid in Central Java of Indonesia showed that the Eo increase of 2500 mm during 95 years resulted in the decrease of growing period by 100 days. In coping with climate change, adjustment of cropping calendar is imperative.